Integrasi Teori dan Praktik dalam Pembelajaran Fikih Berbasis Sistem Pesantren: Analisis Strategi Pembelajaran Perspektif Degeng-Reigeluth - Adam Mustakim; Mashudi; Dyah Nawangsari; Ubaidillah (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2026)
This study aims to analyze the integration of theory and practice in Fiqh learning at KMI Putra Al-Ishlah Bondowoso Islamic Boarding School through the perspective of the Degeng-Reigeluth learning strategy. This research uses a qualitative approach with a case study type. Data is collected through in-depth interviews, observations, and documentation, then analyzed interactively through data condensation, data presentation, and conclusion drawn. The results of the study show that the integration of theory and practice in Fiqh learning takes place as a learning model that is integrated with the 24-hour pesantren system. The integration can be seen in the gradual and contextual organization of materials, the delivery of participatory and habituation-based learning, learning management supported by daily supervision and pesantren culture, and evaluation that emphasizes worship practices and the readiness of students in carrying out religious functions. These findings show that Fiqh learning in Islamic boarding schools is not only oriented to mastering concepts, but also to the formation of habits, discipline, and competencies of student worship in real terms. Thus, this study confirms that pesantren have the potential to become an effective learning ecosystem in integrating cognitive, affective, and psychomotor dimensions in an integrated manner.